Kafka and Wittgenstein The Case for an Analytic Modernism - Schuman, Rebecca (Northwestern University Press, 2015)
In Kafka and Wittgenstein, Rebecca Schuman undertakes the first ever book-length scholarly examination of Ludwig Wittgenstein's philosophy of language alongside Franz Kafka's prose fiction. In groundbreaking readings, she argues that although many readers of Kafka are searching for what his texts mean, in this search we are sorely mistaken. Instead, the problems and illusions we portend to uncover, the important questions we attempt to answer-Is Josef K. guilty? If so, of what? What does Gregor Samsa's transformed body mean? Is Land-Surveyor K. a real land surveyor?- themselves presuppose a bigger delusion: that such questions can be asked in the first place. Drawing deeply on the entire range of Wittgenstein's writings, Schuman cannily sheds new light on the enigmatic Kafka.